Desert wind : a Lena Jones mystery - Webb, Betty (Webb, Betty. Lena Jones mystery., 2012)
When PI Lena Jones' partner, Pima Indian Jimmy Sisiwan, is arrested in the remote town of Walapai Flats in northern Arizona, Lena closes the Desert Investigations office and rushes to his aid. What she finds is a town up in arms over a new uranium mine located only ten miles from the magnificent Grand Canyon. Jimmy's sister-in-law, founder of Victims of Uranium Mining, has been murdered, but the opposing side has taken hits, too. Ike Donohue, the mine's public relations man, is found shot to death, which casts suspicion on Jimmy and his entire family.